A New Cationic Functionalized Pillar[5]arene and Applications for Adsorption of Anionic Dyes. Issue 17 (10th April 2019) - Tian, Huasheng; Wang, Chunyu; Li, Haiying; Deng, Rong; Li, Runan; Meguellati, Kamel
Abstract : Herein, we report a new kind of cationic pillar[5]arene‐based monofunctionalized compound which exists in different conformations in chloroform (pseudorotaxane) and DMSO (open form). This molecule can self‐assemble into vesicles in water and can potentially load negatively charged molecules such as congo red dye in water. The use of these positively charged nanoparticles can be extended to a broad range of applications. Abstract : Herein, we report a new kind of cationic pillar[5]arene‐based monofunctionalized compound which exist in different conformations in chloroform (pseudorotaxane) and DMSO (open form). This molecule can self‐assemble into vesicles in water and can potentially load negatively charged molecules such as congo red dye in water. The use of these positively charged nanoparticles can be extended to a broad range of applications